Statistical analysis of the teacher-psychologist’s work at the College of Music - Krasnoborova, V.S. (Bulletin of Practical Psychology of Education, 2025)
The article is aimed at analyzing the quantitative and qualitative indicators of the results of the teacher-psychologist's work. The data are taken from the experience of working at the Sverdlovsk Tchaikovsky College of Music for the 2021-2022 academic year. Through the statistics analysis, the demand for psychological assistance in college, the specifics of the most relevant requests, the workload of the teacher-psychologist in certain months of the academic year are assessed. The analysis is carried out in accordance with different areas of work indicated in the professional standard of a teacher-psychologist: psychological counseling, correctional and developmental work, psychoprophylaxis, psychological diagnostics, psychological education. The article also identifies some difficulties in the work of a college psychologist teacher. The article also identifies some difficulties in the work of a teacher-psychologist of the college. For example: the difficulties of organizing group correctional and preventive classes. The amount of a psychologist work in this college in the direction of psychological counseling significantly exceeds all others. The number of visits to a psychologist indicates that college students are ready to discuss difficult topics with this specialist. Even with a small number of group sessions with a psychologist, with good contact with students, it is possible to provide psychological assistance to those students who most urgently need it or are in a "risk group" according to the results of socio-psychological testing. В статье анализируются количественные и качественные показатели результатов работы педагога-психолога в Свердловском музыкальном училище им. П.И. Чайковского (колледже) за 2021/2022 учебный год. Через анализ статистики оценивается, насколько востребована психологическая помощь в колледже, специфика наиболее актуальных запросов, загруженность педагога-психолога в определенные месяцы учебного года. Анализ производится в соответствии с разными направлениями работы, обозначенными в профессиональном стандарте педагога-психолога: психологическое консультирование, коррекционно-развивающая работа, психопрофилактика, психологическая диагностика, психологическое просвещение. Также в статье обозначены некоторые трудности в работе педагога-психолога колледжа. Например: сложности организации групповых коррекционно-развивающих и профилактических занятий. Объем работы психолога данного колледжа в направлении психологического консультирования значительно превышает все остальные. Количество обращений к психологу свидетельствует о том, что студенты колледжа готовы обсуждать с данным специалистом сложные темы. Даже при малом количестве групповых занятий с психологом при хорошем контакте со студентами возможно оказывать психологическую помощь тем обучающимся, которые наиболее остро в ней нуждаются или находятся в «группе риска» по результатам социально-психологического тестирования. трудности в работе педагога-психолога колледжа.